Pytania o światopogląd gatunków literackich - Stanisz, Marek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The aim of the given article is to show in what way each literary genre (or reference to a particular genre tradition) evokes a different image of the world, thanks to which it defines an outlook of a particular artistic utterance (the term “outlook” is used here in the meaning assigned by Wilhelm Dilthey). The genre is one of the basic categories referring to literature since the dawn of history. It determines the modality of the world presented of a particular literary work in the sense that it determines the range of themes, plots, motifs as well as artistic solutions (those of composition, stylistics, those referring to time and space) characteristic of a particular literary utterance. Moreover, genres are a form of expressing the reality according to a particular aesthetic and existential dominant (that of the tragic, the comic, pathos, the idyll, heroism etc.).
Questions on the outlook of literary genres
Keywords: światopogląd; gatunek literacki; jakości estetyczne; filozofia i literatura; outlook; literary genre; philosophy and literature; aesthetic dominants